OP0032 Invasion of synoviocytes is inhibited by gene transfer of tnf-bp or il10 in an in vitro invasion model. (1st June 2001) - Pieterman, EJ; Goossens, PH; Laan, WH vd; Huidekoper, AL; Rabelink, MJ; Hoeben, RC; Breedveld, FC; Huizinga, TW
Abstract : Background: In RA fibroblast like synoviocytes (FLS) degrade and invade into adjacent cartilage. An in vivo model is the SCID-mouse/Human cartilage/synoviocyt model (S. Gay). Previous studies indicate that the invasive behaviour of fibroblast like synoviocytes can be tested in vitro in a matrigel transwell system. Matrigel, mainly composed of laminin and collagen IV, serves as a model for cartilage. Objectives: The aim of this study was to compare the invasive behaviour of FLS from RA and osteoarthritis (OA) patients and to investigate the effect of adenoviral (Ad) transfer of genes encoding IL-10 and TNF-binding protein (p55) (TNF-BP) on the invasive behaviour of FLS from RA patients. Methods: FLS from 43 RA and 28 OA patients obtained from synovial tissue harvested at joint replacement surgery, were seeded at confluency in serum free medium on top of a matrigel coated transwell filter with 8 μm pores. Medium with 10% Fetal Calf Serum and 10% Human Serum was used in the lower compartment. Three days post incubation cells were fixated, stained and the invaded synoviocytes on the lower side of the filter were counted. To test the effect of IL10 and TNF-BP, RA synoviocytes were infected overnight with 5, 10, 50 and 100 plaque forming units (pfu)/cel of Ad. IL10, Ad. TNF-BP or Ad. luciferase (negative control) and then tested in the invasion model. Results: Significantly more RA synoviocytes invaded through the matrigel (median = 4035 cells) as compared to OA synoviocytes (median = 1900 cells; p < 0.001). IL10 and TNF-BP gene transfer both resulted in a dose dependent inhibition of invasion with a maximal inhibition of 93.7% (± 10.7) and 86.6% (± 14.5) respectively, while luciferase gene transfer showed a maximal inhibition of 17.6% (± 1.7). Conclusion: In conclusion, the invasive behaviour of FLS can be studied in the matrigel transwell system. This assay discriminates between the invasive behaviour of RA and OA FLS. The invasive behaviour of RA synoviocytes can be strongly inhibited by IL10 indicating that IL10 is able to downregulate the proteins involved in invasive growth. The inhibitive effect of TNF-BP indicates that continuous production of TNF is involved in invasive behaviour of synoviocytes.